Pembelajaran Berbasis Kecerdasan Buatan Terhadap Motivasi Belajar Peserta Didik dalam Pembelajaran Biologi: Sistem Literatur Review - Zahren; Yogica, Relsas; Fitri, Rahmadhani (Alpatih Harapan Semesta, 2025)
Biology learning currently faces challenges in the form of complex material, abstract concepts, and difficult-to-understand language, which impacts students' low learning motivation. This study aims to examine the impact of the application of artificial intelligence (AI) on students' learning motivation in biology education through the Systematic Literature Review (SLR) method. Data were obtained from the Google Scholar, ScienceDirect, and ERIC databases, using the keywords